Effects of ZrO2 crystal structure on the tribological properties of copper metal matrix composites. (October 2019) - Zhou, Haibin; Yao, Pingping; Gong, Taiming; Xiao, Yelong; Zhang, Zhongyi; Zhao, Lin; Fan, Kunyang; Deng, Minwen
Abstract: ZrO2, a promising abrasive to improve tribological properties, is introduced into copper metal matrix composites (Cu-MMCs). Micro-tribological behaviors of ZrO2 in two crystal forms and their effects on the tribological properties of Cu-MMCs were investigated. The results showed that the fragile monoclinic ZrO2 (m-ZrO2 ), exhibiting a high coefficient of friction (COF) and strong bonding with the matrix, evidently enhanced the COF of Cu-MMCs at low and medium braking energy densities (BEDs). Even though the harder cubic ZrO2 (c-ZrO2 ) displayed a relatively low COF and weak bonding with the matrix, it produced significant improvements in wear resistance and COF of Cu-MMCs at high BED. With an increase in BED, the wear mechanisms of Cu-MMCs with m/c-ZrO2 transformed from plough to delamination. Highlights: Tribological properties of m/c-ZrO2 were detected via micro-macro friction tests. m-ZrO2 has a lower hardness, rougher surface and higher COD in micro-friction tests. m-ZrO2 forming a tighter bonding with Cu improved COF of Cu-MMCs at low-medium BED. c-ZrO2 produced improvements in wear resistance and COF of Cu-MMCs at high BED. Wear mechanisms of Cu-MMCs transit from plough to delamination with BED increasing.